USING U-DICTIONARY USING U-DICTIONARY FOR EFFECTIVE SPEAKING CLASS - Hasanah, Maulidatul (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2024)
Speaking achievement is results or abilities obtained from training activities that can be properly demonstrated by using good language. One of the learning media that can support teaching speaking achievement is the U-Dictionary application. The use of U-Dictionary can be used as an effective learning medium, everyone can translate difficult words into the language they want, can be accessed quickly and briefly. The research was Quantitative Research with a Quasi-Experimental Non-equivalent Control Group Design. The population in this research was seventh grade students at MTs Darul Ulum Assurur, which consists of 51 students. The researcher chose a sample of class VIIB (23 students) as the Experimental class and class VIIA (28students) as the Control class. The data collected for this research was from scores of pre-test and post-test. The data were analyzed using the formula of Analysis of Covariance (ANCOVA) with IBM SPSS 27 version. Based on the sample result and hypothesis testing, the score calculated showed the Sig. 0.001 < 0.05, which was interpreted that Ha was accepted while Ho was rejected. The partial eta squared showed 0.222, which means that the mean score obtained by students in the experimental class was 22,2% higher than the control class. It was concluded that there was significant effect of using U-Dictionary application on speaking achievement of MTs Darul Ulum Assurur. There for using U-Dictionary application is effective for English teachers in the speaking class, especially to help students understand vocabulary. Key Words: U-Dictionary, Speaking Achievement